DRY NEEDLING VERSUS STEROID INJECTIONS IN PLANTAR FASCITIS: A META-ANALYSIS. - Prasad, Dr Lal Bahadur; Gupta, Dr Vasudha Gupta; Bhushan, Dr (prof) D P Bhushan (Student’s Journal of Health Research Africa, 2024)
Introduction: Plantar fasciitis, a common cause of heel pain in adults aged 40-60, significantly impacts occupational function. Treatment is categorized into non-invasive and invasive options, with invasive treatments like Local Steroid Injections (LSI) and Dry Needling (DN) used when conservative methods fail. This systematic review aims to critically analyze the literature to ﬁnd the effect of dry needling when compared with corticosteroid injection in treating Plantar Fascitis. Method: This systematic review followed PRISMA guidelines and addressed the question: "Is dry needling more effective than corticosteroid injections for plantar fasciitis?" Databases were searched using specific keywords, articles were screened, and duplicates were removed. Inclusion criteria included English-language RCTs on plantar fasciitis treatment with dry needling or corticosteroid injections. Exclusion criteria comprised unpublished articles and abstracts. Study quality was assessed using the PEDro scale, with scores indicating poor, fair, good, or excellent quality. Guidelines. The principal research question that was studied was “Is dry needling better than corticosteroid injections in treating plantar fascitis?”. Various electronic databases (PubMed, Embase, Web of Science, and the Cochrane Library) were used to search relevant articles using different keywords. Articles were collected altogether and selected based on eligibility criteria. The closing sets of articles were selected after complete screening. Result: The meta-analysis found that both dry needling and corticosteroid injections are effective for short-term relief of plantar fasciitis. Specifically, the p-values indicate significant differences in efficacy, with dry needling demonstrating greater long-term benefits. The individual-level data from these studies could be pooled to compare their measures of clinical relevance, highlighting dry needling’s superiority in maintaining symptom relief over time. Detailed statistical analysis showed p-values less than 0.05 for short-term efficacy and less than 0.01 for long-term outcomes in favor of dry needling. Conclusion: Dry needling is superior to corticosteroid injection in treating plantar fasciitis.